What is Россия Сегодня doing in Serbia? - Reljić, Slobodan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2014)
This paper deals with the emergence of the Russian state-owned media system as the first serious and direct impact on the global monopoly of western “free media”, primarily CNN and BBC. It also establishes that Россия Сегодня is signaling pluralization of the media propaganda reality in a world which is in a deep crisis. The presence of the Chinese CCTV is increasingly noticeable. The role of the global electronic media as the so-called soft power in an ever widening range of conflicts between the great powers, the ways in which it will influence democracy as the global political system and the effects of those tectonic changes on the public opinion in smaller countries like Serbia – is also analysed. Key words: manipulating, anti-CNN, propaganda model, publicity principle, Balkanization, war of images
Keywords: anti-CNN; Media Images; balkanization; principle of publicity; propaganda; manipulation